Alpha 7 nicotinic receptor agonist and positive allosteric modulators improved social and molecular deficits of MK-801 model of schizophrenia in rats - ARICIOĞLU, FEYZA (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Schizophrenia is a common psychiatric disease that cannot be fully treated with current antipsychotic drugs. It has shown that glutamatergic NMDA receptor antagonists such as MK-801 cause schizophrenia-like phenotype in rodents. Recent studies indicated that alpha 7 nicotinic acetylcholine receptor (nAChR) deficits contribute to schizophrenia. Enhancing its activity with agonist or positive allosteric modulators (PAMs) may be a valuable approach for treatment. The certain intracellular pathways such as Akt/Glycogen synthase kinase 3 beta (GSK-3 beta) and phosphodiesterase-4 (PDE-4)/cAMP are associated with the pathogenesis of schizophrenia. In this study, we examined the effect of alpha 7 nAChR agonists and PAMs on the behavioral and molecular phenotype of schizophrenia in the subchronic MK-801 administered rats. Social interaction, the levels of alpha 7 nAChR, and related intracellular pathways (cAMP, PDE4A, PDE4D, p-Akt/Akt, p-GSK-3 beta/GSK-3 beta) were measured by behavioral or ELISA and western blot tests. Subchronic MK-801 administration decreased the following behaviors and increased the avoiding behaviors. However, only alpha 7 nAChR agonist (A-582941) increased the following behavior while alpha 7 nAChR agonist, PAMs (CCMI and PNU-120596), and clozapine decreased the avoiding behavior compared to MK-801. For molecular parameters, MK-801 administration decreased the alpha 7 nAChR, p-Akt/Akt, p-GSK-3 beta/GSK-3 beta expressions, and cAMP levels while it increased PDE4A, PDE4D expressions in the prefrontal cortex. Besides, MK-801 decreased the alpha 7 nAChR, p-GSK-3 beta/GSK-3 beta expressions in the hippocampus. We found clozapine, alpha 7 nAChR agonists, and PAMs reversed the molecular deficits induced by MK-801. Herein, we showed that prefrontal cortex is more sensitive to the devastating effects of subchronic MK-801 administration, especially for PDE4, in rats. In addition to clozapine, alpha 7 nAChR agonists and PAMs found to be beneficial on both social and molecular deficits induced by MK-801 in rats. We suggested that alpha 7 nAChR agonists and PAMs might be valuable approaches to treat negative symptoms of schizophrenia when unmet needs and current limitations considered in this pathology.
Keywords: A-582941; CCMI; PNU-120596; MK-801; alpha 7 nAChR; Schizophrenia; ACETYLCHOLINE-RECEPTORS; NEGATIVE SYMPTOMS; TAU PHOSPHORYLATION; COGNITIVE DEFICIT; ANIMAL-MODELS; ACTIVATION; TRIAL; PHENCYCLIDINE; PNU-120596; RODENTS